Analisis Kapabilitas Inovasi Terhadap Kinerja Umkm Industri Makanan Di Kota Sukabumi - Ilham Budiman; Erry Sunarya; Asep Muhamad Ramdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to analyze the effect of innovation capability on the performance of MSMEs in the food industry in Sukabumi City. The method used in this research is descriptive with a quantitative approach. The sampling technique used in this study is non-probability sampling using a purposive sampling approach. The number of samples used was 187 respondents. The data analysis technique used is multiple linear regression analysis using the SPSS version 26 application. The results of this study indicate that there is a positive and significant effect of innovation capability on MSME performance with a value of 0.253 In conclusion, there is a positive and significant influence innovation capability on MSME performance. Keyword : Innovation Capability, Performance SMEs, Food Industry